MEMORANDUM [CONCERNING CLEAN INDOOR AIR] - WOODSON, WOODSON (Tufts Archival Research Center, 2007)
Memorandum from Walter Woodson to the regional vice-presidents regarding OSHA’s request for information (RFI) on clean indoor air and environmental tobacco smoke (ETS). Requests that vice-president encourage law-makers and restaurateurs to write letters with a pro-tobacco position, stating that they believe ventilation is the solution.